2018
DOI: 10.1039/c7cp08176f
|View full text |Cite
|
Sign up to set email alerts
|

Design of donor–acceptor copolymers for organic photovoltaic materials: a computational study

Abstract: 80 different push-pull type organic chromophores which possess Donor-Acceptor (D-A) and Donor-Thiophene-Acceptor-Thiophene (D-T-A-T) structures have been systematically investigated by means of density functional theory (DFT) and time-dependent DFT (TD-DFT) at the B3LYP/6-311G* level. The introduction of thiophene (T) in the chain has allowed us to monitor the effect of π-spacers. Benchmark studies on the methodology have been carried out to predict the HOMO and LUMO energies and optical band gaps of the D-A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 75 publications
1
37
0
Order By: Relevance
“…The singlet excited states of the oligomers were calculated by using time‐dependent DFT (TDDFT) at the same level of calculation quality. Although it does not include vdW dispersion corrections, B3LYP was successfully utilized for the modeling of CPs including donor–acceptor oligomers reported by Aviyente and coworkers and Seferos and coworkers with its reasonable computational cost and relatively good agreement with experimental results. Band gap was calculated by using two different methods.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The singlet excited states of the oligomers were calculated by using time‐dependent DFT (TDDFT) at the same level of calculation quality. Although it does not include vdW dispersion corrections, B3LYP was successfully utilized for the modeling of CPs including donor–acceptor oligomers reported by Aviyente and coworkers and Seferos and coworkers with its reasonable computational cost and relatively good agreement with experimental results. Band gap was calculated by using two different methods.…”
Section: Methodsmentioning
confidence: 99%
“…Band gap was calculated by using two different methods. Direct difference between the energy of HOMO and energy of LUMO for the optimized ground state were calculated in the first method and the vertical excitation energy of the lowest singlet excited state ( S 0 → S 1 ) were calculated by using TDDFT calculations in the second method …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven different tetramers were modeled as model compounds which are pristine TPD based donor‐acceptor copolymer (pTPD), pristine tetramers of benzochalcogendiazole based donor‐acceptor copolymers with F, O, S and Se substitutions (pPF, pPO, pPS, and pPSe), tetramers with two blocks of TPD based copolymer and two blocks of benzochalcogendiazole based copolymer with F, O, S and Se substitutions (PF, PO, PS, and PSe), tetramers with one and three blocks of benzochalcogendiazole based copolymer with S substitution (PS1, PS3). All calculations were performed for these model tetramers by using the B3LYP hybrid functional 32–34 and 6‐311G* basis set, adopting tight convergence criteria in the Gaussian09 (Revision A.02) software 35 Successful modeling and calculations on the conjugated polymers including donor‐acceptor oligomers reported in the literature by using B3LYP functional 36,37 . Highest occupied molecular orbitals (HOMO), lowest unoccupied molecular orbitals (LUMO), electrostatic potential surfaces (ESP) were mapped onto the optimized geometries for these model compounds.…”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] Commonly, the molecular structures of organic small molecules with intramolecular charge transfer characteristic contain electron donors (D) and electron acceptors (A), which are linked through p-bridge (D-p-A). 21,22 It is reported that modications of the push-pull electronic effect of electron donors and electron acceptors or conjugated linkers are all effective ways to improve the intramolecular charge transfer strength. [23][24][25][26][27][28][29] The 1,3,4-oxadiazole (OXD) ring is a kind of important structural unit in organic photoelectric functional materials for its good luminance, stable thermal performance and excellent electron-transporting properties.…”
Section: Introductionmentioning
confidence: 99%